Innovation and policy process: case of transgenic sweet potato in Kenya - Odame, Hannington; Wafula, David; Kameri-Mbote, Patricia (2002)
Biotechnology is being integrated into the existing science and technology policy process in Kenya. This process is embedded in the country's history of agricultural development, characterised by conventional technology, public goods research, and centralised and hierarchical organisation. This study employs the case study of the transgenic sweet potato project to explore how the development and introduction of modern biotechnology influence institutional and policy change in the generation and retention of (in) appropriate agricultural innovations for smallholders in Kenya. - Reproduced.
Keywords: Biotechnology - Kenya; Agricultural innovations; Agricultural biotechnology